Performance of a water gas shift pilot plant processing product gas from an industrial scale biomass steam gasification plant. (June 2016) - Kraussler, M.; Binder, M.; Fail, S.; Bosch, K.; Hackel, M.; Hofbauer, H.
Abstract: In this paper, the performance of a commercial Fe/Cr based catalyst for the water gas shift reaction was investigated. The catalyst was used in a water gas shift pilot plant which processed real product gas from a commercial biomass steam gasification plant with two different qualities: extracted before and extracted after scrubbing with a rapeseed methyl ester gas scrubber. The performance of the WGS pilot plant regarding these two different gas qualities was investigated. For this reason, extensive chemical analyses were carried out. CO, CO2, CH4, N2, O2, C2 H6, C2 H4, and C2 H2 and H2 S, COS, and C4 H4 S were measured. In addition, GCMS tar and NH3 analyses were performed. Furthermore, the catalyst's activity was observed by measuring the temperature profiles along the reactors of the water gas shift pilot plant. During the 200 h of operation with both product gas qualities, no catalyst deactivation could be observed. A CO conversion up to 93% as well as a GCMS tar reduction (about 28%) along the water gas shift pilot plant was obtained. Furthermore, a specific H2 production of 63 g H2 per kg biomass (dry and ash free) was reached with both product gas qualities. No significant performance difference could be observed. Highlights: A WGS pilot plant was operated with product gas from a commercial biomass gasification plant. The WGS pilot plant was operated with product gas extracted before and extracted after a RME gas scrubber. A commercial Fe/Cr based catalyst was applied. The WGS pilot plant was operated for more than 200 hours. No performance difference and no performance decrease could be observed.